Enhancing the Odontogenic Potential of Human Dental Pulp Stem Cells via Platelet-Rich Plasma Exosomes through Modulation of TGF-β1 and Dentin Sialophosphoprotein - Bagio, Dini Asrianti; Margono, Anggraini; Julianto, Indah; Ricardo, Shalina; Alinda, Sylva Dinie (European Journal of Dentistry, 2025)
Although platelet-rich plasma (PRP) has demonstrated considerable regenerative potential in regenerative endodontic treatment, its clinical efficacy may be limited by the rapid degradation of its bioactive components, leading to inconsistent outcomes. To overcome this challenge, the present study explores the use of nano-sized exosomes derived from PRP—a novel designated as PRP exosomes (PRP-Exo)—as a more stable and targeted biomolecular delivery system to promote odontogenic differentiation within the dentin–pulp complex. The primary objective is to investigate the expression of key odontogenic markers, transforming growth factor-β1 (TGF-β1) and Dentin Sialophosphoprotein (DSPP), in human dental pulp stem cells (hDPSCs) following PRP-Exo treatment.hDPSCs used in this study were biologically stored raw cells harvested at P3-P4. The hDPSCs were starved for 24 hours, then isolated and re-cultured using the enzymatic digestion method until reaching 5 × 104 cells/well. Then, culture media were supplemented using osteogenic conditioned media (OCM): 10 mM β-glycerophosphate, 50 µg/mL ascorbic acid, and 100 Nm dexamethasone. The hDPSCs were seeded in different treatments in the following groups: (1) the control group: hDPSCs in DMEM (Dulbecco's Modified Eagle Medium) + OCM; (2) the experimental group: hDPSCs in DMEM + OCM + 5% PRP-Exo. The PRP-Exo was isolated using the qEV isolation methods (Izon, Advisains) diluted into 5% PRP-Exo. PRP-Exo was analyzed and characterized using nanoparticle tracking analysis (NTA; ViewSizer 3000, Horiba, Kyoto, Japan), followed by specific exosome surface markers CD63+ and CD81 + ). TGF-β1 and DSPP expression of hDPSCs was quantified using an enzyme-linked immunosorbent assay (ELISA) kit (Cat. EL-H0111, Elabscience, Wuhan, Hubei), following the manufacturer's protocol, on an ELISA microplate reader under a wavelength of 405 nm. A qualitative result was obtained by Alizarin red staining up to 21 days.From the NTA result, it was shown that PRP-Exo, which was isolated in this study, has a particle size range of 30 to 150 nm, a homogeneous shape of particles, with several particles after dilution (1.2 × 106 particles/mL). It was also proven that 99.19% PRP-Exo in this study has a specific protein surface marker of exosome (CD 63 + ; CD81 + ). The highest TGF-β1 and DSPP expression of hDPSCs after culturing in PRP-Exo was observed on day 14th, and it was statistically significant (p < 0.05). The qualitative results of the Alizarin red staining test were also consistent.The higher expression of TGF-β1 and DSPP and a larger amount of Ca2+ mineral nodule deposition after 21 days of evaluation of hDPSCs after being treated with PRP-Exo proves that PRP-Exo has potential in the odontogenic process of dentinal pulp complex.
Keywords: platelet-rich plasma; exosomes; dental pulp; stem cells; transforming growth factor; dentin sialophosphoprotein